IMPLIKASI KEBIJAKAN RELAKSASI KREDIT OLEH OJK SELAMA PANDEMI COVID-19 DENGAN DAMPAK BAGI BANK - Viviani, Olinda; Jaya, Febri (Maleo Law Journal, 2022)
Early March 2020, there were more than 100,000 confirmed cases of the CoronavirusDisease 2019 (Covid-19) outbreak in 114 countries with a total death toll of more than 4,000cases. The development of the spread of COVID-19 has a direct or indirect impact on theperformance and capacity of Debtors, including Micro, Small, Medium Enterprises (MSMEs),in fulfilling credit or financing payment obligations, thus potentially disrupting bankingperformance and financial system stability which can affect economic growth. Therefore, toencourage the optimization of the banking intermediation function, maintain financial systemstability, and support economic growth, an economic stimulus policy is needed as acountercyclical impact of the spread of COVID-19. The policies implemented for thepandemic conditions had an impact on banks in their implications for bank performance. Theproblem approach used in this research is the legal approach (Statue Approach) examiningregulations or regulations related to the legal issues under study